Gender Aspects in Animal Production - Kedi Suradisastra; Adriana M Lubis (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2000)
Research on women’s role in animal production are often entangled in physical participation although their problems in agriculture include labor force participation and equilibrium, authority in the household, socialization process and access to information, and technological bias. Socially, the limiting factors in their productivity are social status, job opportunity and status, and their simultan role as compared to men’s sequential role.   Key words : Role, gender, livestock